Analisa Strategi Pengembangan UMKM Flamboyan Menggunakan Metode SWOT - Widodo, Langgeng; Uloli, Hendra; Lahay, Idham Halid (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in national economic development, contributing greatly to job creation and gross domestic product (GDP) value. Potential in the Village: MSMEs in the village have good prospects for increasing community income, empowering individuals, and reducing unemployment. Many MSMEs cannot survive long due to the lack of appropriate business strategies. This study uses SWOT analysis to identify the strengths, weaknesses, opportunities, and threats faced by Flamboyan MSMEs, with the aim of designing appropriate development strategies. Strengths and Weaknesses: Flamboyan MSMEs have an internal strength score of 3.44, indicating that this business is above average in terms of strength. Opportunities and Threats: External factors indicate that the greatest opportunity comes from healthy consumer tendencies, with a weighted value of 0.14286 and a rating of 3.7. Strategy Recommendations: The study recommends that Flamboyan MSMEs develop strategies that utilize strengths, overcome weaknesses, take advantage of opportunities, and reduce threats to improve performance and achieve business goals.